CROSSROADS OF CIVILIZATIONS: THE SOCIAL AND CULTURAL LANDSCAPE OF PRE-ISLAMIC ARAB - Mudin, Imam (Journal of Social Science, 2024)
Objective: This study examines the social and cultural landscape of pre-Islamic Arab societies to uncover the mechanisms shaping social identities, cultural practices, and interethnic interactions, challenging conventional essentialist perspectives. Methods: Adopting a qualitative-interpretive approach with an interactive analysis framework by Miles, Huberman, and Saldaña, the research employs literature reviews, historical document analysis, and cultural narrative reconstruction. Methodological triangulation integrates anthropological, sociological, historical, and psychosocial perspectives to ensure reliability and depth. Results: The findings reveal that pre-Islamic Arab societies exhibited fluid social structures and dynamic identity construction. Ethnic categorization and interethnic interactions were dialectical processes, characterized by continuous negotiation and cultural hybridization. Knowledge systems transcended traditional boundaries, fostering intellectual networks and sustainable cultural adaptation in response to ecological challenges. Novelty: This research provides a nuanced understanding of identity formation as a dynamic construct and dismantles stereotypes about pre-Islamic Arab societies. It highlights the sophistication of their social mechanisms, cultural resilience, and multicultural awareness. The study contributes to a broader academic discourse by presenting a multidimensional analysis that integrates ecological, intellectual, and social factors into the study of identity and cultural practices. These insights redefine the complexity of pre-Islamic Arab societies, offering a significant contribution to understanding multicultural processes and interethnic interactions in historical contexts.